2012
DOI: 10.5812/anesthpain.4399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Low Dose Ketamine in Post Tonsillectomy Pain Relief: A Randomized Trial Comparing Intravenous and Subcutaneous Ketamine in Pediatrics

Abstract: It is useful for the medical education fields and all who are interested in that.Background: Pain control in children is still a therapeutic dilemma. Preschool patients are affected from undesirable effects of postoperative pain more than adults. Tonsillectomy is associated with a high incidence of postoperative pain, not only complicating the recovery, but also delaying patients discharge. Objectives: Despite employing different surgical and anesthetic strategies in post-tonsillectomy pain relief, this is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Many researches have been performed to investigate different analgesics’ effects on post tonsillectomy pain, especially together with acetaminophen. In many studies, relief of early postoperative pain, in first hours of operation, was investigated ( 25 , 26 ). On the other hand, many studies look into postoperative pain after recovery room; in a study held in Finland, it was shown that ketoprofen combined with paracetamol - codeine seems to provide sufficient analgesia during 10 days after surgery ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many researches have been performed to investigate different analgesics’ effects on post tonsillectomy pain, especially together with acetaminophen. In many studies, relief of early postoperative pain, in first hours of operation, was investigated ( 25 , 26 ). On the other hand, many studies look into postoperative pain after recovery room; in a study held in Finland, it was shown that ketoprofen combined with paracetamol - codeine seems to provide sufficient analgesia during 10 days after surgery ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ketamine is superior to bupivacaine in terms of requiring rescue analgesia, promoting a peaceful sleep pattern and the early resumption of feeding [69] . Javid and colleagues [70] demonstrated that both subcutaneous and intravenous injections of ketamine at the end of surgery were safe and effective for post-tonsillectomy pain control without increasing the risk of complications. Two separate studies found the topical application of tramadol and ketamine to be a safe, effective, and easy analgesic approach for decreasing post-tonsillectomy pain [71,72] .…”
Section: Pediatric Usementioning
confidence: 99%
“…The opioid medications are widely used as the main strategy for perioperative pain control, however, associated with side effects like respiratory depression, leading to sedation X Min et al and respiratory depression, and postoperative nausea and vomiting. In response to this, Non-opioid analgesic strategies including non-steroidal anti-inflammatory drugs, local anesthetic infiltration, antibiotics nonvolatile induction and maintenance, alpha-2 agonists, homeopathic drugs, caudal block, and delay of the emergence period have been studied to evaluate the effect on decreasing these complications but the results are not reliably helpful (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%